The relationship between socioeconomic and therapeutic factors with the quality of life among the patients type II diabetes - Mahdi Toroski; Rezvan Rajabzadeh; Melika Niyazi; Hadi Hayati; Habibeh Sadat Shakeri; Maryam Rezapour; Seyed Hamid Hosseini (Journal of Pharmacoeconomics and Pharmaceutical Management, 2017)
Background: It is necessary that we have more information about the quality of life (QOL) of diabetics, their special characteristics and socioeconomical characteristics that affect QOL in type II diabetic patients. The aim of this study was to investigate the QOL in type II diabetic patients and relationship of QOL in type II diabetic patients with socioeconomical and treatment factors in Bojnord City, Iran. Methods: This study was a cross-sectional study. The subjects, in this study, were patients with type II diabetes referring to the diabetes clinic in the city of Bojnord, sampling was done randomly, according to the formula of samples and resources, 218 samples were estimated. For data collection, a two-part questionnaire containing demographic and disease characteristics and QOL questionnaire SF36. After collecting the information and entering data in the software SPSS using χ2 statistics test, one-way ANOVAs, t-test, and correlation coefficient were analyzed. Results: In this study, 218 patients with type II diabetes were analyzed of which 77 (35.3%) were male and 141 (64.7%) were female and most of the cases were married (96.3%). The mean age of the participants was 55.45 ± 11.44 years and also the average weight, body mass index, and duration of disease were 71.94 ± 12.17 kg, 27.18 ± 4.53, and 2720.78 ± 2504.63 days, respectively. The highest average among the eight dimensions of QOL is in physical function. The total score of the QOL was 55.94 ± 18.63. Furthermore, the findings showed that QOL of 66 people (30.3%), 56 people (27.7%), 59 people (27.0%), and 37 people (17.0%) is undesired, poor, good, and desirable, respectively. The results of t-test and ANOVA showed between gender, education, type of treatment and QOL in type II diabetic patients studied; there was a statistically significant difference (P ≤ 0.050). Conclusion: To increase the QOL for diabetics, attention to the self-care training programs and continuous monitoring and regular of patients have an important role.